Correlates of Impaired Global Right Ventricular Function in Patients With a Reperfused Acute Myocardial Infarction and Without Right Ventricular Infarction. (1st April 2013) - Hsu, Shun-Yi; Chang, Shang-Hung; Liu, Chih-Jen; Lin, Jeng-Feng; Ko, Yu-Lin; Cheng, Shih-Tsung; Chou, Hsin-Hua; Chang, Heng-Chia
Abstract : Background: The frequency and clinical correlates of global right ventricular (RV) dysfunction in patients treated with primary percutaneous coronary intervention for a first acute ST-elevation myocardial infarction (STEMI) without a coexisting RV infarction is not well known. Materials and Methods: One hundred seven consecutive patients underwent conventional echocardiography and pulsed-wave tissue Doppler imaging (TDI) within 72 hours after a successful primary percutaneous coronary intervention to assess their RV function. Global RV function was quantified with the RV myocardial performance index (MPI) by pulsed-wave TDI. An abnormal TDI-derived RV MPI was defined as greater than the upper reference limit of 0.55. Results: Global RV dysfunction was present in 18 (17%) of the 107 patients enrolled. The patients with global RV dysfunction had significantly higher glucose levels on admission (216 ± 102 vs 163 ± 86 mg/dL; P = 0.027), higher peak creatine kinase (4027 ± 2171 vs 2660 ± 1980 IU/L; P = 0.014), and more frequently had anterior infarcts (89% vs 58%; P = 0.016) than those without RV dysfunction. Patients with global RV dysfunction also had a significantly lower left ventricular (LV) ejection fraction (45.1 ± 10.8% vs 51.1 ± 9.7%; P = 0.021), a higher global wall motion score index (1.9 ± 0.3 vs 1.7 ± 0.4; P = 0.007), and greater LV MPI (0.65 ± 0.19 vs 0.47 ± 0.11; P = 0.001) than patients without. With the use of multivariate regression analysis, TDI-derived LV MPI (odds ratio [OR], 3.40; 95% confidence interval [CI], 1.20–9.67; P = 0.022), the ratio of transmitral peak early ( E ) to late diastolic filling ( A ) velocities ( E / A ratio) (OR, 0.41; 95% CI, 0.18–0.92; P = 0.031), and admission plasma glucose level (OR, 1.01; 95% CI, 1.0–1.02; P = 0.039) were independently associated with the presence of global RV dysfunction. Conclusions: In patients with a first acute STEMI without an associated RV infarction, depressed global LV function reflected by increased TDI-derived LV MPI, a lower mitral E / A ratio, and a higher glucose level on admission are independent correlates of early global RV dysfunction. Routine assessment of global RV function should be implemented in patients with STEMI with these characteristics.